2015
DOI: 10.1080/19381980.2015.1010983
|View full text |Cite
|
Sign up to set email alerts
|

A vitamin D analog inhibits Th2 cytokine- and TGFβ -induced periostin production in fibroblasts: a potential role for vitamin D in skin sclerosis

Abstract: & Ichiro Katayama (2015) A vitamin D analog inhibits Th2 cytokine-and TGFβ -induced periostin production in fibroblasts: a potential role for vitamin D in skin sclerosis, Dermato-Endocrinology, 7:1, e1010983, DOI: 10.1080DOI: 10. /19381980.2015 Scleroderma is an autoimmune disease characterized by extracellular matrix deposition and inflammation. Topical vitamin D analogs have been reported as effective treatments for scleroderma. We previously reported that a matricellular protein, periostin (POSTN), contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…Vitamin and its analogues have been shown to attenuate fibrosis and delay tumor progression through suppressing the activities of fibroblasts, stellate cells [ 33 35 ]. In scleroderma, the vitamin D analogue inhibits TGF β-induced POSTN expression to reduce fibrosis [ 49 ]. Another study has reported that calcipotriol is capable of inhibiting POSTN expression in pancreatic ductal adenocarcinoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin and its analogues have been shown to attenuate fibrosis and delay tumor progression through suppressing the activities of fibroblasts, stellate cells [ 33 35 ]. In scleroderma, the vitamin D analogue inhibits TGF β-induced POSTN expression to reduce fibrosis [ 49 ]. Another study has reported that calcipotriol is capable of inhibiting POSTN expression in pancreatic ductal adenocarcinoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Although topical vitamin D analog was found useful for localized scleroderma (morphoea), administration of cholecalciferol and/alfacalcidiol (2 mcg/d) has shown no effect or determined improvement in SSc symptoms. [ 26 27 28 ] It is possible that vitamin D deficiency perhaps plays some role in the subsequent development of a well-defined variant from undifferentiated connective tissue disease.…”
Section: Discussionmentioning
confidence: 99%
“…In PF, the ECM receptor expression is increased in interstitial cells, leading to the proliferation and differentiation of interstitial lung cells via signal transduction after ligandreceptor binding, further promoting the synthesis and secretion of fibronectin and collagen. 22,23 The KEGG pathway enrichment revealed accumulation of a large number of DEPs between the model and the control groups in the renin-angiotensin system. Angiotensin II upregulates the expression of cytokine transforming growth factor-β, stimulates fibroblast proliferation, transforms fibroblasts to myofibroblasts and extracellular matrix deposition, resulting in fibrosis.…”
Section: Discussionmentioning
confidence: 99%